2010
DOI: 10.1142/s0219246210000069
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Adventure-Based Counseling Training on the Young Olds

Abstract: It is commonly believed that Adventure-based Counseling (ABC) training is intended for young people who are active and energetic. The St. James' Settlement (an NGO) in Hong Kong, however, believes that such training can also have positive effects on the young olds (individuals aged 50–65). A group of young old trainees was recruited from the community to help implement related activities to elderly members of this NGO. Their general health condition, levels of life satisfaction, optimism, and self-efficacy wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Regarding the different modes of Tier 2 Programs, although previous studies showed that ABC and VTS were the two major modes involved [ 9 – 13 ], comparative analyses were not meaningful because of the variations in the unique design of programs for different schools. As far as ABC is concerned, it is an approach that attempts to integrate adventure, wilderness, and experiential learning, as well as individual and group counseling [ 18 21 ]. According to this approach, when an adolescent with a disequilibrium in personal development is put into an environment that is strange and requires cooperation (i.e., adventure environment), the tasks designed to provide adventure experiences will lead to transformation in the participant, including changes in self-confidence and self-understanding, as well as cooperation with others [ 21 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the different modes of Tier 2 Programs, although previous studies showed that ABC and VTS were the two major modes involved [ 9 – 13 ], comparative analyses were not meaningful because of the variations in the unique design of programs for different schools. As far as ABC is concerned, it is an approach that attempts to integrate adventure, wilderness, and experiential learning, as well as individual and group counseling [ 18 21 ]. According to this approach, when an adolescent with a disequilibrium in personal development is put into an environment that is strange and requires cooperation (i.e., adventure environment), the tasks designed to provide adventure experiences will lead to transformation in the participant, including changes in self-confidence and self-understanding, as well as cooperation with others [ 21 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…As far as ABC is concerned, it is an approach that attempts to integrate adventure, wilderness, and experiential learning, as well as individual and group counseling [ 18 21 ]. According to this approach, when an adolescent with a disequilibrium in personal development is put into an environment that is strange and requires cooperation (i.e., adventure environment), the tasks designed to provide adventure experiences will lead to transformation in the participant, including changes in self-confidence and self-understanding, as well as cooperation with others [ 21 – 25 ]. According to Schoel et al [ 26 ], ABC promotes life skills in the participants, including communication skills, cooperation, and decision-making and problem-solving skills.…”
Section: Introductionmentioning
confidence: 99%